Pathways to interdisciplinarity: A technical report exploring collaborative interdisciplinary working in the transition pathways consortium - Tom Hargreaves; Jacquelin Burgess (University of East Anglia, The Centre for Social and Economic Research on the Global Environment (CSERGE), 2010)
Questions about the future of the energy system in the UK have, in recent years become deeply entangled with a number of previously discrete intellectual, commercial and policy domains. Not least, the emergence of what Hulme (2009) refers to as 'upper-case Climate Change' to distinguish this discourse from the routine dynamics of weather and climate systems, with its imperative massively to reduce global production of greenhouse gases within the next 50-60 years, has added a sense of urgency and a different rationale to underpin future strategies for managing the energy sector than has previously been the case. Each IPCC assessment report has provided stronger justification for the need for action; many governments in the developed world have responded by seizing opportunities to review, redirect and /or renew their energy policies and provide a framework for future investment by the private sector (see, for example, DTI 2003, 2006, 2007) whilst seizing opportunities to benefit from the rapid deployment of technological innovations to support the growth of 'clean energy' systems.
Keywords: 330; Transition Pathways consortium